PENGARUH PENDIDIKAN DAN PELATIHAN (DIKLAT) KEPEGAWAIAN TERHADAP KINERJA ORGANISASI BADAN KEPEGAWAIAN DAERAH(BKD) KABUPATEN HALMAHERA UTARA (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT :The role of the Regional Employment Board is not optimally manage personnelresources, it is necessary to improve the quality of personnel resources in improving the professionalperformance of the apparatus, especially for professional development related to management skills. Thepopulation in this study were all officers or employees in Sub Tobelo North Halmahera recorded the numberof officers or employees who have as many as 25 civil servants.The research method that I use in this study is a quantitative research methods. The methods andapproach used by the consideration that examined in this study is quite actual and factual and intends toexamine the relationship or influence between the variables.The results of product moment correlation analysis and simple regression, can be tested the hypothesisthat "Education and training influence on Organizational Performance Regional Employment Board ofNorth Halmahera District", the 1% significance level, indicating that education and training are veryinfluential on Organizational Performance, especially in the office of the Regional Employment BoardHalmahera north, the magnitude of these effects can be observed from the analysis of determination, wherethe coefficient of determination obtained for 0.894 which may be interpreted that the magnitude of theinfluence of education and training to organizational performance 89.4%. These results indicate that thevariation change of organizational performance by an average of 41.79, or 69.65% is determined by a variety89.4%, while theï‚±of factors change Education and Training of remaining 10.6% influenced. data analysisshowed that between education and training the performance of the organization has linkage relationshipsand influences that are contributive as well as the very real or significant.Keywords: education and training, organizational performance